2012
DOI: 10.1002/jbm.a.34313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of locally administered insulin on bone formation in non‐diabetic rats

Abstract: The possibility to control bone formation would be favorable in many areas of medicine, where bone defects is still a major challenge. Insulin has been suggested to exert both systemic and local anabolic effects in bone tissues. This raised the question whether locally administrated insulin could provide new therapeutic strategies for patients with local bone defects and impaired bone healing. The aim of this study was to evaluate bone formation in non-diabetic rats when local insulin is administered. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Either general insulin administration [7] or local infiltration at the implantebone interface [8] may naturally improve the success of oral implantation in diabetic rats. Malekzadeh et al demonstrated that insulin therapy can neutralize the effects of diabetes on bone healing and can enhance peri-implant bone formation in the disease [9]. Although existing evidence suggests that insulin has potential benefits with respect to osteogenesis under conditions of DM, the underlying mechanisms responsible for this effect are unclear.…”
Section: Introductionmentioning
confidence: 96%
“…Either general insulin administration [7] or local infiltration at the implantebone interface [8] may naturally improve the success of oral implantation in diabetic rats. Malekzadeh et al demonstrated that insulin therapy can neutralize the effects of diabetes on bone healing and can enhance peri-implant bone formation in the disease [9]. Although existing evidence suggests that insulin has potential benefits with respect to osteogenesis under conditions of DM, the underlying mechanisms responsible for this effect are unclear.…”
Section: Introductionmentioning
confidence: 96%
“…In the authors' previous study, the insulin coated titanium implants demonstrated a larger bone area (BA) around implants, compared to uncoated controls. One hypothesis then was that the significantly higher BA for insulin‐coated implants was due to an insulin release effect, that is, insulin acting on bone cells in the periphery.…”
Section: Discussionmentioning
confidence: 94%
“…The thickness of the immobilized insulin on the reference Si‐samples ( n = 5) was measured at three different spots on every sample by null ellipsometry, programmed for measurements in air and calculated as reported in our previous study (HeNe laser equipped Auto‐Ell III, Rudolph Research, USA). The immobilized layer thickness was calculated according to the McCrackin evaluation algorithm and converted to an approximate adsorbed amount per unit area by the de Feijter's formula .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 However, the plasma half-life of insulin is only 5-15 minutes; so, in vivo applications are limited due to short periods of insulin activity. 26,27 In this study, we optimized controlled release of bioactive insulin from nanospheres within the composite scaffold and maintained high insulin concentration at the defect site. To investigate the influence of the composite scaffolds on cell proliferation and osteogenic differentiation, human BMSCs were cultured on the scaffolds.…”
mentioning
confidence: 99%